Guía para el desarrollo de la psicomotricidad de los niños/as de 2 a 3 años a través del juego - Chimarro Imbago, Eva María (2015)
The psychomotoroccupies a veryimportantplacein early childhood education, especially in early childhood, children - girlspracticeiton a daily basis, either:running, jumping, climbing, rolling, playing with objects.You can also applyvariousaimed at developingcoordination,balance and orientationgames. That iswhythepresent thesis focuses onthePreparationand Application ofplayactivitiestodevelopskills: walking, running,jumping, throwing, climbing, combineskills, run and jump, throw and catch, throw and run,forwhichtwoactivitiesaresuggestedforeachskillfordevelopingmotorskillsinchildrentwo to threeyearsinCIBV"Cananvalle". During thisprocesshas been consideredtheoreticalaspectsfromconcepts, functions, methods, techniques, strategies and resources to be used intheTeaching Learning Process. The psychomotorconsistsofall activities thatrequiregrossmotorcoordinationitselftobeenhancedproperly.